Sosialisasi Penerapan Biosecurity sebagai Upaya Pencegahan Penularan Penyakit pada Ternak Sapi di Desa Luhulely Kecamatan Pulau Letti Kabupaten Maluku Barat Daya - Arnold Ismael Kewilaa; Albertus Sairudy; Demianus Adrian Dolaitery; Edeleta Koupun; Yulma Enggelina Beay; Santi Silvia Naskata; Ellias Andreas Lekiwona; Rambu Ngoma Ataratu; Rudy Y. Hitipeuw; Femsi Boimau; Grasela Wontopur; Chiristina Niken Ayu Sariwating; Yosvia Vivi Lekan; Gramsi Tunay; Emi Agustina Katipana (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
The purpose of this activity is to socialize the implementation of biosecurity as an effort to prevent disease in cattle in Luhulely Village, Pulau Letti District, Southwest Maluku Regency. This activity was carried out using a socialization method involving beef cattle farmers and all Luhulely Village staff. The implementation of the activity was divided into 2 sessions, namely a material presentation session and an interactive discussion session. Some general steps in implementing biosecurity include the following: access management, animal movement control, cleanliness and sanitation, waste management, animal health monitoring, and vaccination. This socialization activity was attended by approximately 20 participants consisting of beef cattle farmers and several Luhulely Village staff. Several important things that can be concluded from the implementation of this activity are as follows: the majority of farmers showed an increased understanding of the importance of biosecurity after participating in the socialization, the farmers expressed their readiness to implement various biosecurity measures, such as quarantine of new livestock, waste management, and provision of adequate sanitation facilities in the livestock area, and several farmers requested further assistance regarding the implementation of more detailed biosecurity, including correct livestock vaccination techniques. The conclusion of this activity is that the socialization of biosecurity implementation on cattle farms is expected to increase farmers' awareness and understanding of maintaining livestock health and preventing disease transmission. Through proper biosecurity implementation, it is hoped that healthy, more productive, and sustainable livestock conditions will be created.